Differential Regulation of Myocardial E3 Ligases and Deubiquitinases in Ischemic Heart Failure - Kristin Klaeske; Maria Dix; Volker Adams; Khalil Jawad; Sandra Eifert; Christian Etz; Diyar Saeed; Michael A. Borger; Maja-Theresa Dieterlen (Life, 2021)
The pathological changes of ubiquitination and deubiquitination following myocardial infarction (MI) and chronic heart failure (CHF) have been sparsely examined. We investigated the expression of muscle-specific E3 ubiquitin ligases and deubiquitinases in MI and CHF. Therefore, mice were assigned to coronary artery ligation for 3 days or 10 weeks as well as for sham operation (each n = 10). Expression of E3 ligases (MAFBX, MURF1, CHIP, ITCH, MDM2) and deubiquitinases (A20, CYLD, UCH-L1, USP14, USP19) was determined. After MI and in CHF, the mRNA expression of MURF1, CHIP and MDM2 (all p < 0.05) was decreased. Protein expression analyses revealed that ITCH expression decreased in CHF (p = 0.01), whereas MDM2 expression increased in MI (p = 0.02) and decreased in CHF (p = 0.02). Except for USP19 mRNA expression that decreased at 3 days and 10 weeks (both p < 0.01), the expression of other deubiquitinases remained unaffected after MI and CHF. The expression of myocardial E3 ligases is differentially regulated following MI, raising the question of whether an upstream regulation exists that is activated by MI for tissue protection or whether the downregulation of E3 ligases enables myocardial hypertrophy following MI.